2013
DOI: 10.1111/phn.12055
|View full text |Cite
|
Sign up to set email alerts
|

Women, Infant and Children (WIC) Peer Counselor Contact with First Time Breastfeeding Mothers

Abstract: Women's decision to initiate breastfeeding is significantly associated with WIC peer counselor contacts. Continued WIC peer counselor program services may increase breastfeeding initiation rates among WIC participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…USDA mandated WIC breastfeeding support programs, which include peer counseling, are intended to increase breastfeeding initiation, exclusivity, and duration, and are an important component of the revised WIC program in NYS. Studies have shown that breastfeeding initiation increases after WIC peer counselor contact [26], and both breastfeeding initiation and the prevalence of exclusive breastfeeding increased following implementation of the revisions to the WIC food package in California [27,28] and New York [10]. In addition, messages about reducing screen time are vigorously promoted in New York [8,9] and the proportion of WIC participants reporting two or fewer hours of screen time increased slowly but steadily in the years following implementation of the revised WIC program in New York [10].…”
Section: Discussionmentioning
confidence: 99%
“…USDA mandated WIC breastfeeding support programs, which include peer counseling, are intended to increase breastfeeding initiation, exclusivity, and duration, and are an important component of the revised WIC program in NYS. Studies have shown that breastfeeding initiation increases after WIC peer counselor contact [26], and both breastfeeding initiation and the prevalence of exclusive breastfeeding increased following implementation of the revisions to the WIC food package in California [27,28] and New York [10]. In addition, messages about reducing screen time are vigorously promoted in New York [8,9] and the proportion of WIC participants reporting two or fewer hours of screen time increased slowly but steadily in the years following implementation of the revised WIC program in New York [10].…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding Peer Counseling Programs are offered as a means of providing educational, emotional and social support for new breast-feeding mothers (59,64) . Recent research has revealed that Breastfeeding Peer Counseling Programs have had positive effects on increasing breast-feeding initiation and continuation for black mothers enrolled in WIC (68,69) . Breastfeeding Peer Counseling Programs have discovered that black women tend to place high value on breast pumps as a matter of convenience and a way to exert control over breast-feeding (67) .…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that providing peer counseling for women, especially in populations that have problems with breastfeeding initiation and duration, can improve the mother and the child's health (McCoy, Geppert, Dech, & Richardson, ). Campbell, Wan, Speck, and Hartig () suggest that future studies include mothers without breastfeeding experience who are supported by peer counseling groups and mothers who do not use peer counseling groups to compare breastfeeding commencement and other related variables (Campbell et al, ). In another study by Srinivas et al, 120 women were studied for up to 4 months, showing that breastfeeding was improved in all women during the study period (Srinivas, Benson, Worley, & Schulte, ).…”
Section: Introductionmentioning
confidence: 99%